The Influence Of Using Concept Map Through Cooperative Learning Think Pair Share On The Learning Outcomes On Eleventh Grade Science Students Of Sman 1 Dua Koto Pasaman - Maiyesi Yenti; Indang Dewata; Mawardi Mawardi (Postgraduate School, Universitas Negeri Padang, 2020)
The research aims to study the effect of using concept map through cooperative learning Think Pair Share (TPS) on th learning outcomes on eleventh grade science students of SMAN 1 Dua Koto Pasaman in terms of students’ initial knowledge. This was a quasy experiment. Sample are choose using cluster random sampling techniques. Data are analyzed using t-test. Based on the average value of student learning outcomes in the experiment group, 75% or 27 students have reached the minimum completeness criteria. The calculation of the hypothesis tcount (3.042) > ttable (1.995), it is means Ho rejected and H1 is received. It can be concluded that the learning outcomes of students taught using concept map through cooperative learning TPS signicantly different from learning outcomes of students taught with concept maps through conventional learning. The conclusion of this study are there is an effect of the use of concept map in cooperative learning Think Pair Share (TPS) on the learning outcomes on eleventh grade science student in SMAN 1 Dua Koto Pasaman.